2022
DOI: 10.1002/jmv.27641
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term immunity in convalescent Syrian hamsters provides protection against new‐variant SARS‐CoV‐2 infection of the lower but not upper respiratory tract

Abstract: COVID-19 vaccines provide high levels of protection against severe disease and hospitalization due to severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2) infection. Vaccination may be less effective in preventing shedding of infectious viruses from otherwise immune patients. In this study, we describe breakthrough infections and shedding of infectious viruses in convalescent hamsters without significant replication in the lower respiratory tract following reinfection by Alpha and Delta variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
(25 reference statements)
1
5
0
Order By: Relevance
“…Mucosal COVID-19 vaccines have been experimentally shown to reduce upper respiratory shedding, but not transmission, when assessed in a single contact transmission chain setting [30][31][32]. In addition, hamster studies have shown that previous infection protects against disease, but not upper respiratory tract replication, after homologous and heterologous reinfection [27,[34][35][36]. Similar dynamics were observed in our experimental setup.…”
Section: Discussionsupporting
confidence: 77%
“…Mucosal COVID-19 vaccines have been experimentally shown to reduce upper respiratory shedding, but not transmission, when assessed in a single contact transmission chain setting [30][31][32]. In addition, hamster studies have shown that previous infection protects against disease, but not upper respiratory tract replication, after homologous and heterologous reinfection [27,[34][35][36]. Similar dynamics were observed in our experimental setup.…”
Section: Discussionsupporting
confidence: 77%
“…Whether this reflects an intrinsic neurovirulence of the virus or the limitation of the mouse model will need to be investigated. Second, we and others have shown that immunity acquired through natural infection does not lead to sterilizing immunity in nasal cavity [53][54][55][56] . Hence, even if immunization with WA1-ΔPRRA-ΔORF6-8-Nsp1 K164A/H165A significantly reduces SARS-CoV-2 infection and pathology, to achieve sterilizing immunity in the upper respiratory tract may not be a realistic goal.…”
Section: Discussionmentioning
confidence: 84%
“…Viral RNA was extracted from infected cell lysates using TRIzol reagent (Thermo Fisher) and QIAgen RNeasy kit followed by quantitative reverse transcription polymerase chain reaction (qRT-PCR) using primer/probes specific for the E region as described previously [ 8 ]. Focus-forming assays were conducted in H1299-hACE2 cells as described previously [ 4 ].…”
Section: Methodsmentioning
confidence: 99%